Metodologi Penafsiran Sayyed Abu A’la Al-Maududi Dalam Tafsir Tafhīmul Qur’ān - Nurfadliyati (QOF, 2022)
This article described the Tafhi>mul Qur'an interpretation method written by Sayyed Abu A'la Al-Maududi from Pakistan. Efforts to interpret the Qur'an if examined from its history began in tandem with the activities of the Rasullullah's da'wah activities that conveyed the teachings of Islam that were revealed in the form of revelation. However, after the death of Rasullullah, the companions and generations after him were required to do ijtihad to understand the verses of the Qur'an. The goal is none other than so that the Qur'an as a guide to life can be applied in everyday life, as well as so that the Qur'an is able to answer the problems of the people. For this reason, along with the passage of time and regional differences, interpretation has distinctive characteristics and differences in interpretation. Even interpretation efforts continue until now. One of the interpretations that appeared in the 20th century was written by Sayyid Abu A’la al-Maududi with the title Tafhīmul Qur'ān. This article is a qualitative research that is a descriptive-analytic library research. The results of this study revealed that the tafsir method used in tafsir Tafhīmul Qur'ān was the tahlili and ijmali method, which explains from various aspects delivered in ijmali. In terms of interpretation sources, this tafsir can be categorised as tafsir bil ma'tsur and bil ra'yi with al-adabi ijtima'i and 'ilmi style.